Exploring Ottoman sovereignty tradition, image and practice in the Ottoman imperial household, 1400-1800 - Murphey, Rhoads (Hambledon Continuum, 2008)
This book is a lively political anthropology of Ottoman sovereignty, an account of the rituals, ceremonies, and projection of the sultans' power over the period 1480-1820.